Imām Mālik Between Khabar Al-Aḥād Al-Ṣaḥīḥ and ‘Amal 'Ahl al-Madīnah: An Applied Study - Mariah Bassam Mohammed Abd al Rahman (Journal of Islamic and Religious Studies, 2020)
The importance of this study is to reveal the truth of the case of the response of Imam Malik (179 e) - the leader of the School of Archeology - the story of the atheists by violating the work of the people of the city; The study resulted in the results of the most important response of this lawsuit for several reasons, the first of which is that the work of the people of the city is a frequent occurrence, Rather, the imam has an approach based on the introduction of the frequent on the individual, and that many of the issues of work are supported by the correct hadeeth, and the one that is contrary to it is apparent, and it is permissible to combine or say the copies when proven.